TATA KELOLA DAN KINERJA KEUANGAN PADA KANTOR KECAMATAN WANEA KOTA MANADO - Walangitan, Nivi; Morasa, Jenny; Mawikere, Lidia M. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
Whether or not a government institution runs well or poorly provided services depends on the leadership policy in its management. The purpose of this study was to determine public governance and financial performance at the Wanea District Office. The analytical method used is qualitative analysis with Primary data. The results showed that (1) the implementation of transparency in the Wanea District Office was good. (2) The implementation of accountability in the form of the ability to present government information openly, (3) quickly and accurately to the public,(4) the ability to provide satisfactory services to the public, the ability to provide space for the community, the ability to explain and account for any public policy proportionally and (5) the provision of facilities for the public to assess government performance . So the implementation of the principle of accountability in Wanea District is good. Financial performance in the Wanea District Office is good.